2017
DOI: 10.1126/scitranslmed.aam7816
|View full text |Cite
|
Sign up to set email alerts
|

BCAS1 expression defines a population of early myelinating oligodendrocytes in multiple sclerosis lesions

Abstract: BCAS1 expression identifies newly formed and actively myelinating oligodendrocytes in development, adulthood, and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 182 publications
(166 citation statements)
references
References 49 publications
(69 reference statements)
8
154
0
4
Order By: Relevance
“…6b). These genes are involved in the differentiation of oligodendrocyte-precursor towards mature oligodendrocytes [38][39][40][41]. On the same trend, we found two new clusters of "unknown" cells from the bladder in MCA data-set ( Fig.…”
Section: Revealing New Minor Classes Using Pathway Scores and Annotatsupporting
confidence: 65%
“…6b). These genes are involved in the differentiation of oligodendrocyte-precursor towards mature oligodendrocytes [38][39][40][41]. On the same trend, we found two new clusters of "unknown" cells from the bladder in MCA data-set ( Fig.…”
Section: Revealing New Minor Classes Using Pathway Scores and Annotatsupporting
confidence: 65%
“…Through co‐localization analyses and EdU incorporation assays, we showed that Pcdh17it is a specific marker for newly forming imOLs in developing and adult forebrain in mice (Figure ). Compared to two recently reported imOL markers Enpp6 (Xiao et al, ) and Bcas1 (Fard et al, ), Pcdh17it expression seems to better align with an intermediate stage between OPs and mature OLs, hence providing higher specificity for imOLs (Figures , and ; Figures S1 and S5a–d). Enpp6 is also weakly expressed in mature OLs with high levels of co‐localization (~90%) with CC1, and Bcas1 was also detected in some mature OLs, agreeing with data from a recently published single cell RNA‐seq database for OL lineage cells (Marques et al, ; Marques et al, ; Figure S5c–d).…”
Section: Discussionmentioning
confidence: 58%
“…4 | DISCUSSION 4.1 | Pcdh17it as a specific marker for immature OLs Through co-localization analyses and EdU incorporation assays, we showed that Pcdh17it is a specific marker for newly forming imOLs in developing and adult forebrain in mice ( Figure 6). Compared to two recently reported imOL markers Enpp6 and Bcas1 (Fard et al, 2017), Pcdh17it expression seems to better align with an intermediate stage between OPs and mature OLs, hence providing higher specificity for imOLs (Figures 1,3,and 6;.…”
Section: Statisticsmentioning
confidence: 55%
“…These premyelinating oligodendrocytes are generated in such a large number that only around half of the cells manage to myelinate axons while the remaining are eliminated by apoptosis (Barres et al, ). Premyelinating oligodendrocytes are distinguished by their high expression of the breast carcinoma amplified sequence 1 (BCAS1) and ectonucleotide pyrophosphatase/phosphodiesterase 6 (ENPP6) protein, which serve as markers for oligodendrocytes in an intermediate stage of differentiation, between early progenitors and mature cells (Fard et al, ; Xiao et al, ). Most likely these premyelinating oligodendrocytes have a narrow time window, in which they compete for survival factors possibly secreted by or expressed on unmyelinated axons (Czopka, Ffrench‐Constant, & Lyons, ).…”
Section: How Is Grey Matter Myelination Regulated?mentioning
confidence: 99%
“…Longitudinal two‐photon imaging of oligodendrocytes showes that myelination occurs for at least 12 months with only half of the final myelin generated until 4 months of age (Hill, Li, & Grutzendler, ; Hughes et al, ). These data concur with the observation that BCAS1 + premyelinating cells are generated until at least 1 year of age in mice (Fard et al, ). In humans BCAS1 + cells were mainly found in the first year of postnatal white matter development, but were also present, at low levels, in the frontal human cortex into adulthood.…”
Section: How Is Grey Matter Myelination Regulated?mentioning
confidence: 99%